Propylene-based polymer composition and molded article

A propylene-based polymer composition with optimized miscibility and rigidity addresses cracking issues in molded articles, enhancing environmental sustainability.

JP7619134B2Active Publication Date: 2025-01-22JAPAN POLYPROPYLENE CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021064538
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-04-24
Filing Date
2021-04-06
Publication Date
2025-01-22
Estimated Expiration
2041-04-06

AI Technical Summary

Technical Problem

Existing propylene polymer compositions containing biomass polyethylene suffer from poor miscibility, leading to cracking issues in molded articles, despite their potential environmental benefits.

Method used

A propylene-based polymer composition with a biomass content of 8.4 to 49% is formulated using specific propylene-based polymers and biomass polyethylene, optimized with metallocene catalysts and nucleating agents to enhance miscibility and rigidity, preventing cracking.

Benefits of technology

The composition achieves molded articles with excellent rigidity and no cracking, contributing to reduced environmental impact while maintaining performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007619134000008
    Figure 0007619134000008
  • Figure 0007619134000001
    Figure 0007619134000001
  • Figure 0007619134000002
    Figure 0007619134000002
Patent Text Reader

Abstract

To provide a propylene-based polymer composition that provides a molding that is excellent in the toughness and is not cracked even when biomass polyethylene is contained and that has the degree of the biomass of 8.4 to 49%, and the molding.SOLUTION: A propylene-based polymer composition comprises, in total of 100 pts.mass, 26 to 87 pts.mass of propylene-based copolymer (a) satisfying conditions (H-i) to (H-ii), 3 to 25 pts.mass of propylene-based copolymer (b) satisfying the conditions (A-i) to (A-iii) and 10 to 49 pts.mass of the biomass polyethylene (c) and has the degree of biomass of 8.4 to 49%: (H-i) propylene homo-polymer or propylene-based copolymer having α-olefin content smaller than 1 wt.%, (H-ii) MFR is 0.5 to 100 g / 10 minutes; (A-i) propylene-α-olefin random copolymer; (A-ii) α-olefin content is 1 wt.% or larger and smaller than 3 wt.%; and (A-iii) MFR is 0.5 to 80 g / 10 minutes.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a propylene-based polymer composition having a biomass content of 8.4 to 49% and a molded article thereof, and more particularly to a propylene-based polymer composition that gives a molded article having excellent rigidity and not cracking even when it contains biomass polyethylene. In the present invention, "crack" means that it is divided into several parts when a force is applied. In addition, "not crack" means any of the following: (1) It does not split into several parts without any fissures (cracks, fissures). (2) A fissure (crack) forms but does not separate into several parts. [Background technology]

[0002] Propylene-based resins are characterized by their excellent rigidity, heat resistance, moldability, transparency and chemical resistance, and are therefore used in a wide range of applications, including various industrial materials, automobile-related parts, various medical and cosmetic containers, daily necessities, films and fibers. Meanwhile, environmental pollution caused by plastics has become a problem in recent years, and how to deal with this issue is a challenge. One of the ways to deal with this problem is to use carbon-neutral plant-derived plastics (biomass plastics). Plant-derived polypropylene has also been considered, but is not currently on the market, and the addition of biomass polyethylene to polypropylene is being considered (see, for example, Patent Documents 1 and 2).

[0003] However, a mixture obtained by mixing polypropylene and biomass polyethylene and melt-kneading the mixture has poor miscibility, and molded articles obtained from the mixture tend to crack. For this reason, a polypropylene composition that has excellent miscibility even when it contains biomass polyethylene is desired. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2019-34519 A [Patent Document 2] JP 2016-27171 A Summary of the Invention [Problem to be solved by the invention]

[0005] In view of the above-mentioned conventional technology, an object of the present invention is to provide a propylene-based polymer composition having a biomass content of 8.4 to 49%, which gives a molded article having excellent rigidity and no cracking even when it contains biomass polyethylene, and a molded article thereof. [Means for solving the problem]

[0006] The present inventors have conducted extensive research and have found a propylene-based polymer composition having a biomass content of 8.4 to 49%, which, when used with a specific propylene-based polymer mixture, gives molded articles that are excellent in rigidity and do not crack even when containing biomass polyethylene, and a molded article thereof, and have completed the present invention. That is, the present invention provides a propylene-based polymer composition having a biomass degree of 8.4 to 49% as described below, and a molded article thereof.

[0007] [1] A propylene-based polymer composition comprising 26 to 87 parts by weight of a propylene-based (co)polymer (a) satisfying the following conditions (Hi) to (H-ii), 3 to 25 parts by weight of a propylene-based copolymer (b) satisfying the following conditions (Ai) to (A-iii), and 10 to 49 parts by weight of a biomass polyethylene (c), the total of which is 100 parts by weight, and the biomass degree is 8.4 to 49%. (Hi) A propylene homopolymer or a propylene-based copolymer consisting of propylene and an α-olefin with a content of less than 1% by weight. (H-ii) The melt flow rate (hereinafter sometimes abbreviated as MFR) according to JIS K7210 (230° C., 2.16 kg load) is in the range of 0.5 to 100 g / 10 min. (Ai) Propylene-α-olefin random copolymer. (A-ii) The α-olefin content is in the range of 1% by weight or more and less than 3% by weight. (A-iii) MFR is in the range of 0.5 to 80 g / 10 min. [2] The propylene-based polymer composition according to [1], in which the propylene-based copolymer (b) satisfies the following conditions (A-iv) to (Av): (A-iv) Metallocene-based propylene-ethylene random copolymer. (Av) The melting peak temperature (Tm) is in the range of 126°C or higher and less than 142°C. [3] A propylene-based polymer composition comprising 0.01 to 0.6 parts by weight of a nucleating agent based on 100 parts by weight of the propylene-based polymer composition according to [1] or [2]. [4] A molded article obtained by using the propylene polymer composition according to any one of [1] to [3]. Effect of the Invention

[0008] Molded articles produced using the propylene-based polymer composition of the present invention having a biomass content of 8.4 to 49% contribute to reducing environmental impact and are useful because they provide molded articles that are excellent in rigidity and do not crack even when they contain biomass polyethylene. In particular, injection molded articles are very useful. [Brief description of the drawings]

[0009] [Figure 1] Figure 1 shows the cracking test in the MD and TD directions, which was carried out by making cuts in an injection test piece of 120 mm × 120 mm × 2 mm. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The propylene-based polymer composition of the present invention contains 26 to 87 parts by weight of a propylene-based (co)polymer (a) satisfying the following conditions (Hi) to (H-ii), 3 to 25 parts by weight of a propylene-based copolymer (b) satisfying the following conditions (Ai) to (A-iii), and 10 to 49 parts by weight of a biomass polyethylene (c), totaling 100 parts by weight, and has a biomass degree of 8.4 to 49%, which is characterized by contributing to a reduction in environmental load and not causing a decrease in performance. (Hi) A propylene homopolymer or a propylene-based copolymer consisting of propylene and an α-olefin with a content of less than 1% by weight. (H-ii) The melt flow rate (hereinafter sometimes abbreviated as MFR) according to JIS K7210 (230° C., 2.16 kg load) is in the range of 0.5 to 100 g / 10 min. (Ai) Propylene-α-olefin random copolymer. (A-ii) The α-olefin content is in the range of 1% by weight or more and less than 3% by weight. (A-iii) MFR is in the range of 0.5 to 80 g / 10 min. The propylene polymer composition and the molded article of the present invention will be described in detail below.

[0011] [1] Components constituting the propylene polymer composition (1) Propylene (co)polymer (a)

[0012] (i) α-olefin of propylene (co)polymer (a) The propylene (co)polymer (a) used in the propylene polymer composition of the present invention is preferably a propylene homopolymer, a propylene copolymer comprising propylene and an α-olefin having a content of less than 1% by weight, or a mixture thereof. The propylene-based (co)polymer (a) is preferably a homopolymer from the viewpoint of rigidity, and is preferably a random copolymer consisting of propylene and an α-olefin from the viewpoint of transparency. The α-olefin used for copolymerization includes α-olefins having 2 to 20 carbon atoms excluding propylene, such as ethylene, 1-butene, 1-hexene, and 1-octene. The α-olefins copolymerized with propylene may be one type or two or more types. Among these, ethylene and 1-butene are preferred. Ethylene is more preferred. These propylene-based polymers may be used in combination of two or more types. From the viewpoint of rigidity, it is preferred that the content of the α-olefin is less than 1% by weight.

[0013] Specific examples of the propylene copolymer include binary or ternary copolymers in which small amounts of comonomers are optionally combined, such as propylene-ethylene copolymer, propylene-1-butene copolymer, propylene-1-hexene copolymer, propylene-1-octene copolymer, propylene-ethylene-1-butene copolymer, propylene-ethylene-1-hexene copolymer, and propylene-1-butene-1-octene copolymer.

[0014] The α-olefin content used in the propylene (co)polymer (a) is preferably less than 1 wt%, more preferably less than 0.8 wt%, and even more preferably less than 0.5 wt%. When the α-olefin content is less than 1 wt%, the rigidity is improved and there is no risk of deformation when the containers are stacked. Here, the contents of propylene and α-olefin are as follows: 13 This is a value measured by the C-NMR method. Equipment: JEOL-GSX270 manufactured by JEOL Co., Ltd. Concentration: 300mg / 2mL Solvent: ortho-dichlorobenzene

[0015] (ii) Melt flow rate (MFR) of propylene (co)polymer (a) The propylene-based (co)polymer (a) used in the present invention has a melt flow rate (MFR) in the range of 0.5 to 100 g / 10 min, preferably 5 to 60 g / 10 min, and more preferably 10 to 40 g / 10 min, according to JIS K7210 (230°C, 2.16 kg load). A melt flow rate (MFR) of 0.5 g / 10 min or more improves moldability and provides a product that is satisfactory. A melt flow rate of 100 g / 10 min or less improves mechanical strength. The melt flow rate (MFR) can be easily adjusted by adjusting the temperature and pressure, which are the polymerization conditions for the propylene (co)polymer (a), or by controlling the amount of hydrogen added in a method in which a chain transfer agent such as hydrogen is added during polymerization.

[0016] (iii) Stereoregularity of the propylene (co)polymer (a) When the propylene (co)polymer (a) used in the present invention is a propylene homopolymer, the isotactic pentad fraction is preferably 0.90 or more, more preferably 0.94 to 0.98. When the isotactic pentad fraction is 0.90 or more, the rigidity is satisfactory. Here, the isotactic pentad fraction is 13 This value is measured by the proton decoupling method using C-NMR.

[0017] (iv) Catalyst for Propylene (Co)polymer (a) The catalyst used in the propylene (co)polymer (a) used in the present invention is not particularly limited, but it is preferable to use a stereoregular catalyst, such as a Ziegler catalyst or a metallocene catalyst.

[0018] Examples of Ziegler catalysts include two-component catalysts consisting of a transition metal component, such as a titanium halide compound such as titanium trichloride, titanium tetrachloride, or trichloroethoxytitanium, or a contact product of the titanium halide compound with a magnesium compound such as a magnesium halide, and an organometallic component, such as an alkylaluminum compound or its halide, hydride, or alkoxide, and further three-component catalysts in which an electron donor compound containing nitrogen, carbon, phosphorus, sulfur, oxygen, silicon, or the like is added to any of the above components.

[0019] The metallocene catalyst is preferably a supported type. A particularly preferred example of the supported metallocene catalyst is an ion-exchange layered silicate in which the support also functions as a promoter. Specifically, the catalyst is obtained by combining the following components [A], [B], and the optional component [C].

[0020] Component [A] Metallocene complex Compounds of transition metals in groups 4 to 6 of the periodic table containing at least one conjugated five-membered ring ligand ·Component [B] Promoter Ion-exchangeable layered silicate Component [C] Organoaluminum compound

[0021] Component [A] Metallocene complex Specifically, the compound represented by the following formula [I] can be used as the above component [A]. Q(C5H 4-a R 1 a )(C5H 4-b R 2 b )MXY···[I] In formula [I], Q represents a linking group that bridges two conjugated five-membered ring ligands. M represents a transition metal of Groups 4 to 6 of the periodic table, and among these, titanium, zirconium and hafnium are preferable. X and Y each independently represent hydrogen, halogen, a hydrocarbon group having 1 to 20 carbon atoms, an oxygen-containing hydrocarbon group having 1 to 20 carbon atoms, a nitrogen-containing hydrocarbon group having 1 to 20 carbon atoms, a phosphorus-containing hydrocarbon group having 1 to 20 carbon atoms, or a silicon-containing hydrocarbon group having 1 to 20 carbon atoms.

[0022] R 1 and R 2 each independently represents a hydrocarbon group having 1 to 20 carbon atoms, a halogen, a halogen-containing hydrocarbon group having 1 to 20 carbon atoms, an alkoxy group, an aryloxy group, a silicon-containing hydrocarbon group, a phosphorus-containing hydrocarbon group, a nitrogen-containing hydrocarbon group, or a boron-containing hydrocarbon group. 1 or 2 R 2 are bonded to C4~C 10 It may form a ring. In particular, it is preferable to form a 6-membered ring or a 7-membered ring, and to form an indene ring or an azulene ring together with the above-mentioned conjugated 5-membered ring. a and b are integers satisfying 0≦a≦4 and 0≦b≦4. Examples of the bonding group Q bridging two conjugated five-membered ring ligands include an alkylene group, an alkylidene group, a silylene group, and a germylene group. These may have hydrogen atoms substituted with alkyl groups, halogens, etc. A silylene group is particularly preferred.

[0023] Specific preferred examples of the metallocene complex include the following compounds: (1) Methylenebis(cyclopentadienyl)zirconium dichloride (2) Methylene(cyclopentadienyl)(3,4-dimethylcyclopentadienyl)zirconium dichloride (3) Isopropylidene(cyclopentadienyl)(3,4-dimethylcyclopentadienyl)zirconium dichloride (4) Ethylene(cyclopentadienyl)(3,5-dimethylpentadienyl)zirconium dichloride (5) Methylenebis(indenyl)zirconium dichloride (6) Ethylenebis(2-methylindenyl)zirconium dichloride (7) Ethylene 1,2-bis(4-phenylindenyl)zirconium dichloride (8) Ethylene(cyclopentadienyl)(fluorenyl)zirconium dichloride

[0024] (9) Dimethylsilylene(cyclopentadienyl)(tetramethylcyclopentadienyl)zirconium dichloride (10) Dimethylsilylenebis(indenyl)zirconium dichloride (11) Dimethylsilylenebis(4,5,6,7-tetrahydroindenyl)zirconium dichloride (12) Dimethylsilylene(cyclopentadienyl)(fluorenyl)zirconium dichloride (13) Dimethylsilylene(cyclopentadienyl)(octahydrofluorenyl)zirconium dichloride (14) Methylphenylsilylenebis[1-(2-methyl-4,5-benzo(indenyl)]zirconium dichloride (15) Dimethylsilylenebis[1-(2-methyl-4,5-benzoindenyl)]zirconium dichloride (16) Dimethylsilylenebis[1-(2-methyl-4H-azulenyl)]zirconium dichloride (17) Dimethylsilylenebis[1-(2-methyl-4-(4-chlorophenyl)-4H-azulenyl)]zirconium dichloride (18) Dimethylsilylenebis[1-(2-ethyl-4-(4-chlorophenyl)-4H-azulenyl)]zirconium dichloride (19) Dimethylsilylenebis[1-(2-ethyl-4-naphthyl-4H-azulenyl)]zirconium dichloride

[0025] (20) Diphenylsilylenebis[1-(2-methyl-4-(4-chlorophenyl)-4H-azulenyl)]zirconium dichloride (21) Dimethylsilylenebis[1-(2-methyl-4-(phenylindenyl))]zirconium dichloride (22) Dimethylsilylenebis[1-(2-ethyl-4-(phenylindenyl))]zirconium dichloride (23) Dimethylsilylenebis[1-(2-ethyl-4-naphthyl-4H-azulenyl)]zirconium dichloride (24) Dimethylgermylenebis(indenyl)zirconium dichloride (25) Dimethylgermylene(cyclopentadienyl)(fluorenyl)zirconium dichloride As for other transition metal compounds of Groups 4, 5, and 6, such as titanium compounds and hafnium compounds, the same compounds as those mentioned above are also preferred. These compounds may be used in combination with the catalyst component and catalyst of the present invention.

[0026] Component [B] Co-catalyst (ion-exchange layered silicate) The ion-exchangeable layered silicate is not limited to a natural product, but may be an artificially synthesized product. A clay compound can be used as the ion-exchangeable layered silicate, and specific examples of the clay compound include the following layered silicates described in "Clay Mineralogy" by Haruo Shiramizu, Asakura Publishing (1995). (A) Kaolin group, such as dickite, nacrite, kaolinite, anoxicite, metahalloysite, and halloysite, whose main constituent layers are 1:1 type structures; serpentine group, such as chrysotile, lisardite, and antigorite (a) Smectite group such as montmorillonite, sauconite, beidellite, nontronite, saponite, hectorite, stevensite, etc., vermiculite group such as vermiculite, mica group such as mica, illite, sericite, glauconite, etc., attapulgite, sepiolite, palygorskite, bentonite, pyrophyllite, talc, chlorite group, etc., whose main constituent layers are 2:1 type structures

[0027] The silicate used in the present invention may be a layered silicate having a mixed layer of the above (a) and (b). In the present invention, the main component silicate is preferably a silicate having a 2:1 type structure, more preferably a smectite group silicate, and particularly preferably montmorillonite. The main component means the component that is most abundant.

[0028] The activity of these silicates can be improved by chemically treating them with an acid, a salt, an alkali, an oxidizing agent, a reducing agent, an organic solvent, or the like. The acid treatment can remove impurities on the surface of the ion-exchangeable layered silicate particles, exchange interlayer cations, and also dissolve some or all of the cations such as Al, Fe, Mg, etc. in the crystal structure. The acid used in the acid treatment includes hydrochloric acid, nitric acid, sulfuric acid, etc., and is preferably an inorganic acid, and particularly preferably sulfuric acid. There is no particular restriction on the acid treatment conditions, but the conditions are preferably such that an aqueous solution of 5 to 50% by weight of acid is reacted at a temperature of 60 to 100°C for 1 to 24 hours, and the acid concentration may be changed during the reaction. After the acid treatment, washing is usually performed. Washing is an operation for separating and removing the acid contained in the treatment system from the ion-exchangeable layered silicate.

[0029] It is preferable to select and use salts containing specific cations for the salt treatment. The type of cation is preferably a monovalent to tetravalent metal cation, and particularly preferably Li, Ni, Zn, or Hf cations. Specific examples of salts include the following: Examples of compounds with a Li cation include LiCl, LiBr, Li2SO4, Li3(PO4), Li(ClO4), Li2(C2O4), LiNO3, Li(OOCCH3), and Li2(C4H4O4). Examples of compounds with a Ni cation include NiCO3, Ni(NO3)2, NiC2O4, Ni(ClO4)2, NiSO4, NiCl2, and NiBr2. Examples of compounds with a cation of Zn include Zn(OOCH3)2, Zn(CH3COCHCOCH3)2, ZnCO3, Zn(NO3)2, Zn(ClO4)2, Zn3(PO4)2, ZnSO4, ZnF2, ZnCl2, ZnBr2, and ZnI2. Examples of compounds with a cation of Hf include Hf(OOCCH3)4, Hf(CO3)2, Hf(NO3)4, Hf(SO4)2, HfOCl2, HfF4, HfCl4, HfBr4, and HfI4.

[0030] After the chemical treatment, drying is performed. Generally, the drying temperature can be 100 to 800°C, and high temperature conditions that cause structural destruction (for example, 800°C or higher, although this depends on the heating time) are not preferred. Even if the structure is not destroyed, the characteristics change depending on the drying temperature, so it is preferable to change the drying temperature depending on the application. The drying time is usually 1 minute to 24 hours, preferably 5 minutes to 4 hours, and the atmosphere is dry air, dry nitrogen, dry argon, or reduced pressure. There is no particular limitation on the drying method, and various methods can be used.

[0031] Component [C] Organoaluminum compound The organoaluminum compound of component [C] is a component that is optionally used as necessary, and is most preferably a compound represented by the following formula [II]: (AlR 4 p X 3-p ) q [II] In formula [II], R 4 represents a hydrocarbon group having 1 to 20 carbon atoms, and X represents a halogen, hydrogen, an alkoxy group, or an amino group. p is an integer of 1 to 3, and q is an integer of 1 or 2. R 4 is preferably an alkyl group, and when X is an alkoxy group, it is preferably an alkoxy group having 1 to 8 carbon atoms, and when X is an amino group, it is preferably an amino group having 1 to 8 carbon atoms. Among these, preferred are trialkylaluminum where p=3 and q=1 and dialkylaluminum hydride where p=2 and q=1. More preferred are R 4is a trialkylaluminum having 1 to 8 carbon atoms.

[0032] The organoaluminum compounds can be used alone or in combination. The organoaluminum compounds can be added not only during catalyst preparation but also during prepolymerization or main polymerization.

[0033] (v) Production method of propylene (co)polymer (a) Examples of the method for producing the propylene-based (co)polymer (a) include a slurry polymerization method using an inert solvent in the presence of the above catalyst, a solution polymerization method, a gas phase polymerization method substantially without using a solvent, and a bulk polymerization method using a polymerization monomer as a solvent. For example, in the case of a slurry polymerization method, the polymerization can be carried out in an inert hydrocarbon or liquid monomer such as n-butane, isobutane, n-pentane, isopentane, hexane, heptane, octane, cyclohexane, benzene, toluene, or xylene. The polymerization temperature is usually -80 to 150°C, and preferably 40 to 120°C. The polymerization pressure is preferably 1 to 60 atm (0.10 to 6.08 MPa), and the molecular weight of the resulting propylene-based (co)polymer (a) can be adjusted with hydrogen or other known molecular weight regulators. The polymerization is carried out by a continuous or batch reaction, and the conditions may be those usually used. Furthermore, the polymerization reaction may be carried out in one stage or in multiple stages. When using a metallocene catalyst, it is desirable to carry out a prepolymerization treatment before carrying out the main polymerization. As the monomer to be subjected to the prepolymerization, an α-olefin such as ethylene, propylene, 1-butene, 1-hexene, etc., a diene compound such as 1,3-butadiene, etc., or a vinyl compound such as styrene, divinylbenzene, etc. can be used. This prepolymerization is preferably carried out in an inert solvent under mild conditions, and is desirably carried out so that 0.01 to 1,000 g, preferably 0.1 to 100 g, of polymer is produced per 1 g of solid catalyst (the total of components [A] and [B]).

[0034] The polymerization reaction is carried out in the presence or absence of a solvent such as an inert hydrocarbon such as butane, pentane, hexane, heptane, toluene, or cyclohexane, or a liquefied α-olefin. In the present invention, it is desirable to maximize the amount of polymer produced per solid catalyst (if the solid catalyst is prepolymerized, this does not include the polymer produced by the prepolymerization). In order to increase the amount of polymer produced, it is desirable to set both the polymerization temperature and the polymerization pressure relatively high.

[0035] Usually, the polymerization temperature is selected from 60 to 90°C, and the polymerization pressure is selected from about 1.5 to 4 MPa. In particular, in the case of bulk polymerization, the polymerization temperature is preferably selected from 60 to 80°C, and the polymerization pressure is preferably selected from about 2.5 to 4 MPa in correlation with the temperature. On the other hand, in the case of gas phase polymerization, the polymerization temperature is preferably selected from 70 to 90°C, and about 1.5 to 4 MPa. Furthermore, the polymer production amount per solid catalyst can be increased by increasing the residence time of the solid catalyst, but if it is too long, the productivity is affected. The preferred residence time is 1 to 8 hours, more preferably 1 to 6 hours. It is desirable to set the polymerization conditions so that the polymer production amount per 1 g of the solid catalyst including the carrier is 20 kg or more, preferably 25 kg or more, more preferably 30 kg or more. Hydrogen may be present in the polymerization system as a molecular weight regulator. Furthermore, the polymerization may be carried out in multiple stages by changing the polymerization temperature, the concentration of the molecular weight regulator, etc.

[0036] In the present invention, after the completion of the polymerization, the obtained propylene-based (co)polymer (a) is preferably washed with an inert saturated hydrocarbon solvent such as propane, butane, pentane, hexane, or heptane, or a liquid α-olefin, more preferably with an inert hydrocarbon solvent having 3 or 4 carbon atoms or a liquid α-olefin. The washing method is not particularly limited, and any known method can be used, such as decantation of the supernatant after contact treatment in a stirring tank, countercurrent washing, or separation from the washing liquid using a cyclone. A deactivating agent may be added before or at the same time as washing. There is no particular limitation on the deactivating agent, and water, alcohols such as methanol, ethanol, and isopropanol, ketones such as acetone and methyl ethyl ketone, and mixtures thereof can be used. As such a propylene-based (co)polymer (a), commercially available products can be used, such as those available under the trade names WINTEC and NOVATEC PP from Japan Polypropylene Corporation.

[0037] (vi) Molecular weight distribution (Mw / Mn) and weight average molecular weight (Mw) of the propylene (co)polymer (a) The molecular weight distribution [weight average molecular weight (Mw) / number average molecular weight (Mn)] of the propylene (co)polymer (a) used in the present invention, as measured by gel permeation chromatography (GPC), is preferably 1.5 to 7.0. The lower limit of the molecular weight distribution is preferably 2.0 or more, more preferably 3.0 or more, and the upper limit is preferably 6.0 or less, more preferably 5.0 or less. If the lower limit of the molecular weight distribution is more than a certain level, the range of conditions for producing and purifying the propylene-based (co)polymer (a) is broadened, which is preferable since it improves production efficiency. On the other hand, if the upper limit is less than a certain level, it indicates that the length of the molecular chain is very uniform, which is preferable since it reduces the content of relatively low molecular weight components such as unreacted monomers, dimers, low molecular weight compounds, amorphous components, and oligomers, which are thought to cause the generation of volatile components.

[0038] The weight average molecular weight (Mw) of the propylene-based (co)polymer (a) used in the present invention is preferably in the range of 100,000 to 600,000. When the weight average molecular weight Mw is 600,000 or less, molding is easy. On the other hand, when the weight average molecular weight Mw is 100,000 or more, the amount of low crystallinity components is reduced, mold contamination, bleed-out, solvent elution, etc. are suppressed, and the impact resistance of the molded product is improved, which is practical.

[0039] (vii) Average elution temperature (T 50) and dissolution dispersion (σ) When a metallocene catalyst is used, the average elution temperature (T 50 ) is preferably 90 to 105°C, and the dissolution dispersion (σ) is preferably 9°C or less. Here, the average elution temperature is a value based on the elution curve of the polymer obtained by temperature rising elution fractionation using o-dichlorobenzene as a solvent, and represents the temperature at which the cumulative mass of the eluted polymer is 50% by mass. The elution dispersion is the value of σ when the cumulative mass elution amount I(t) is defined as being expressed by the following formula (1), assuming that the elution amount obtained by temperature rising elution fractionation follows a normal probability distribution with respect to the elution temperature.

[0040]

number

[0041] (2) Propylene-based copolymer (b) (i) Catalyst for Propylene-Based Copolymer (b) The catalyst used for the propylene copolymer (b) is not particularly limited, but it is preferable to use a stereoregular catalyst. Examples of the stereoregular catalyst include Ziegler catalysts and metallocene catalysts. The Ziegler catalyst and metallocene catalyst are the same as those mentioned above. It is preferable to use a metallocene catalyst that is less likely to crack when containing the biomass polyethylene (c).

[0042] (ii) α-olefin of propylene-based copolymer (b) The α-olefin content of the propylene-based copolymer (b) used in the present invention is in the range of 1% by weight or more and less than 3% by weight, preferably 1 to 2.9% by weight, more preferably 1.5 to 2.4% by weight. When it is 1% by weight or more, the impact resistance is sufficient, and when it is less than 3% by weight, high rigidity can be maintained and the mold releasability during injection molding is good. The α-olefin used for copolymerization includes α-olefins having 2 to 20 carbon atoms other than propylene, such as ethylene, 1-butene, 1-hexene, and 1-octene. The α-olefin copolymerized with propylene may be one type or two or more types. Among these, ethylene and 1-butene are preferred. Ethylene is more preferred. In addition, these propylene-based copolymers may be used in a mixture of two or more types. Specific examples of the propylene-based copolymer include binary or ternary copolymers in which any amount of comonomer is combined, such as propylene-ethylene copolymer, propylene-1-butene copolymer, propylene-1-hexene copolymer, propylene-1-octene copolymer, propylene-ethylene-1-butene copolymer, propylene-ethylene-1-hexene copolymer, and propylene-1-butene-1-octene copolymer. Such a propylene-based copolymer (b) satisfies the condition of being a metallocene-based propylene-α-olefin random copolymer. The metallocene-based propylene-α-olefin random copolymer is a propylene-α-olefin random copolymer obtained by polymerization using a metallocene catalyst.

[0043] Moreover, the propylene-based copolymer (b) used in the present invention preferably satisfies the following conditions (A-iv) to (Av). (A-iv) Metallocene-based propylene-ethylene random copolymer. (Av) The melting peak temperature (Tm) is in the range of 126°C or higher and less than 142°C. The metallocene-based propylene-ethylene random copolymer is a propylene-based copolymer (b) obtained by polymerizing propylene as the main component and ethylene as an α-olefin using a metallocene catalyst.

[0044] (iii) MFR of propylene copolymer (b) The melt flow rate (MFR: 230° C., 2.16 kg load) of the propylene copolymer (b) is in the range of 0.5 to 80 g / 10 min. When the melt flow rate (MFR: 230°C, 2.16 kg load) of the propylene-based copolymer (b) used in the present invention is 0.5 g / 10 min or more, molding is easy, and when it is 80 g / 10 min or less, the relatively low molecular weight components in the propylene-based copolymer (b) are unlikely to bleed onto the surface of the molded product, resulting in a good appearance. The melt flow rate (MFR) can be easily adjusted by adjusting the temperature and pressure, which are the polymerization conditions for the propylene-based copolymer (b), or by controlling the amount of hydrogen added in a method in which a chain transfer agent such as hydrogen is added during polymerization.

[0045] (iv) Tm of propylene copolymer (b) The melting peak temperature (Tm) of the propylene-based copolymer (b) used in the present invention is 126°C or higher and lower than 142°C, preferably in the range of 128 to 141°C, and more preferably in the range of 130 to 140°C. When the melting peak temperature (Tm) is 126°C or higher, the rigidity and moldability are good, and when it is lower than 142°C, the transparency is good. The specific method for measuring the melting peak temperature (Tm) is to use a differential scanning calorimeter (DSC) to take a 5.0 mg sample, hold it at 200°C for 5 minutes, crystallize it at a temperature drop rate of 10°C / min to 40°C, and then melt it at a temperature increase rate of 10°C / min. The peak position of the curve drawn when the sample is melted at this temperature increase rate is taken as the melting peak temperature Tm (°C).

[0046] (v) Content of propylene copolymer (b) The propylene-based polymer composition of the present invention contains 26-87 parts by weight of a propylene-based (co)polymer (a), 3-25 parts by weight of a propylene-based copolymer (b), and 10-49 parts by weight of a biomass polyethylene (c), totaling 100 parts by weight. The propylene-based copolymer (b) is obtained by adding 3-25 parts by weight to 26-87 parts by weight of the propylene-based (co)polymer (a) and 10-49 parts by weight of the biomass polyethylene (c). However, the propylene-based polymer composition containing the propylene-based (co)polymer (a), the propylene-based copolymer (b), and the biomass polyethylene (c) is 100 parts by weight. When the content of the propylene-based copolymer (b) is 3 parts by weight or more, the impact resistance is improved, and when it is 25 parts by weight or less, the rigidity is improved, which is preferable.

[0047] (vi) Method for producing propylene copolymer (b) The method for producing the propylene-based copolymer (b) is not particularly limited, and any method for producing a propylene-based copolymer may be used. The catalyst used for the production is not particularly limited, but it is preferable to use a stereoregular catalyst. Examples of the stereoregular catalyst include Ziegler catalysts and metallocene catalysts. It is preferable to use a metallocene catalyst that is less likely to crack when containing the biomass polyethylene (c). The metallocene catalyst is the same as that mentioned above. Such a propylene-based copolymer (b) may be commercially available, for example, Vistamax, a product of Exxon Mobil Corporation, or WELNEX, WINTEC, or NOVATEC PP, a product of Japan Polypropylene Corporation.

[0048] (3) Biomass polyethylene (c) Plant-derived ethylene, which is the raw material monomer of the biomass polyethylene (c) used in the present invention, can be obtained by fermenting plant raw materials such as sugar cane with microorganisms to produce ethanol, which is then heated in the presence of a catalyst to cause an intramolecular dehydration reaction. Biomass polyethylene (c) is a polymer obtained by polymerizing monomers containing plant-derived ethylene as the main component. The raw material monomers of biomass polyethylene (c) do not have to contain 100% plant-derived ethylene. This is because the environmental impact can be reduced by using plant-derived ethylene as part of the monomers. As the biomass polyethylene (c), a homopolymer obtained by homopolymerizing plant-derived ethylene or a copolymer obtained by copolymerizing plant-derived ethylene and an α-olefin can be used. The number of carbon atoms of the α-olefin is not particularly limited, but 1-butene, 1-hexene, or 1-octene is preferable. Furthermore, petroleum-derived ethylene may be contained.

[0049] Examples of polyethylenes used as the biomass polyethylene (c) include high density polyethylene (HDPE), medium density polyethylene (MDPE), low density polyethylene (LDPE) and linear low density polyethylene (LLDPE). These polyethylenes can be used alone or in combination of two or more. The density of the high density polyethylene is preferably 0.940 to 0.965 g / cm 3 The density of the medium density polyethylene is preferably 0.925 to 0.940 g / cm.3 This range is preferable because it improves rigidity. Among the above polyethylenes, it is preferable to use at least one of low density polyethylene and linear low density polyethylene, which will provide a sufficient transparency improving effect. The density of the low-density polyethylene is preferably 0.910 to 0.920 g / cm 3 and more preferably 0.913 to 0.917 g / cm 3 The density is 0.910g / cm 3 If the density is 0.920 g / cm or more, the rigidity is improved, which is preferable. 3 If it is less than this, the transparency improving effect becomes sufficient, which is preferable. The density of the linear low density polyethylene is preferably 0.895 to 0.925 g / cm. 3 and more preferably 0.900 to 0.917 g / cm 3 The density is 0.895g / cm 3 If the density is 0.925 g / cm or more, the rigidity is improved, which is preferable. 3 If it is less than this, the transparency improving effect becomes sufficient, which is preferable.

[0050] The ratio of plant-derived carbon to the total carbon in biomass polyethylene (c) is called the bio-content. 14 It can be determined by measuring the concentration of C. In other words, there is a certain percentage of 14 C, while the carbon in petroleum-based resins contains 14 Since it does not contain C, it is contained in biomass polyethylene (c). 14 The bio-content can be calculated by measuring the C concentration. Specifically, if all the carbon in the biomass polyethylene (c) is derived from petroleum, the bio-content will be 0%, and if all the carbon in the biomass polyethylene (c) is derived from plants, the bio-content will be 100%. 14 Test methods for measuring the concentration of C include ASTM D6866. The biomass polyethylene (c) used preferably has a melt flow rate in the range of 0.21 to 72 g / 10 min according to ASTM D1238 (190° C., 2.16 kg load).

[0051] The weight ratio of the biomass polyethylene (c) used in the propylene-based copolymer is 10 to 49 parts by weight, preferably 15 to 40 parts by weight. When it is 10 parts by weight or more, an effect of reducing environmental load can be expected, and when it is 49 parts by weight or less, sufficient rigidity of the product can be obtained. (Here, the propylene-based polymer composition containing 26 to 87 parts by weight of the propylene-based (co)polymer (a), 3 to 25 parts by weight of the propylene-based copolymer (b), and 10 to 49 parts by weight of the biomass polyethylene (c) is 100 parts by weight.) An example of such biomass polyethylene (c) is "Green PE" (product name manufactured by Braskem).

[0052] (4) Biomass ratio The biomass ratio (%) in the present invention is a numerical value calculated by the following formula. Biomass ratio (%) = [{A × (B ÷ 100)} / C] × 100 Formula (2) A: Weight of biomass polyethylene (c) B: Bio content (%) of the bio-polyethylene used C: Weight of the propylene polymer composition The biocontent (%) of the biomass polyethylene (c) can be measured and calculated according to ASTM D6866.

[0053] (5) Nucleating agent The propylene polymer composition of the present invention may contain a nucleating agent preferably in an amount of 0.01 to 0.6 parts by weight based on 100 parts by weight of the propylene polymer composition. Various common known nucleating agents can be used, such as sterically hindered amide compounds, metal salts of organic dicarboxylic acids, metal salts of organic monocarboxylic acids, sorbitol or its derivatives, nonitol or its derivatives, metal salts of diterpene acids, or polymer nucleating agents. Among them, it is particularly preferable to contain a nucleating agent represented by the following formula (1) in order to realize transparency.

[0054] [ka] (1) (In the formula, n is an integer of 0 to 2, and R 1 ~R 5 are each independently the same or different and are hydrogen, halogen, alkyl having 1 to 20 carbon atoms, alkenyl having 2 to 20 carbon atoms, alkoxy having 1 to 20 carbon atoms, alkoxycarbonyl having 1 to 20 carbon atoms, or phenyl; R 6 is an alkyl group having 1 to 20 carbon atoms. Among the nucleating agents represented by formula (1), a representative commercially available product is Milad NX8000J (manufactured by Milliken & Company). Its chemical structure is as shown in the following formula (1-1). The molecular weight of this nucleating agent is 484. This substance is extremely stable thermally and chemically, and has the excellent characteristic of hardly decomposing thermally even at molding temperatures. This is very preferable because there is no problem of decomposition products bleeding out onto the surface of the molded product and deteriorating its appearance.

[0055] [ka] (1-1)

[0056] The content of the nucleating agent represented by formula (1) contained in the propylene-based polymer composition of the present invention is preferably 0.1 to 0.6 parts by weight, more preferably 0.2 to 0.4 parts by weight, and even more preferably 0.3 to 0.4 parts by weight, based on 100 parts by weight of the propylene-based polymer composition. When the content of the nucleating agent represented by formula (1) is 0.1 parts by weight or more, it is expected that rigidity and transparency are exhibited, and when it is 0.6 parts by weight or less, there is less concern about bleeding onto the surface of the molded article, which is advantageous in terms of cost-effectiveness (cost performance) and elution in terms of rigidity and transparency.

[0057] (6) Other additives In the propylene polymer composition of the present invention, in addition to the above-mentioned components, various additives used as stabilizers for propylene polymers, such as various antioxidants, ultraviolet absorbers, light stabilizers, and neutralizing agents, can be blended. Specifically, examples of the antioxidant include phosphorus-based antioxidants such as bis(2,6-di-t-butyl-4-methylphenyl)pentaerythritol diphosphite, di-stearyl-pentaerythritol diphosphite, bis(2,4-di-t-butylphenyl)pentaerythritol diphosphite, tris(2,4-di-t-butylphenyl)phosphite, tetrakis(2,4-di-t-butylphenyl)-4,4'-biphenylene diphosphonite, and tetrakis(2,4-di-t-butyl-5-methylphenyl)-4,4'-biphenylene diphosphonite. antioxidants, 2,6-di-t-butyl-p-cresol, tetrakis[methylene(3,5-di-t-butyl-4-hydroxyhydrocinnamate)]methane, 1,3,5-trimethyl-2,4,6-tris(3,5-di-t-butyl-4-hydroxybenzyl)benzene, tris(3,5-di-t-butyl-4-hydroxybenzyl)isocyanurate, and other phenol-based antioxidants; and di-stearyl-β,β'-thio-di-propionate, di-myristyl-β,β'-thio-di-propionate, di-lauryl-β,β'-thio-di-propionate, and other thio-based antioxidants.

[0058] Examples of the ultraviolet absorbent include 2-hydroxy-4-n-octoxybenzophenone, 2-(2'-hydroxy-3',5'-di-t-butylphenyl)-5-chlorobenzotriazole, and 2-(2'-hydroxy-3'-t-butyl-5'-methylphenyl)-5-chlorobenzotriazole.

[0059] Light stabilizers include n-hexadecyl-3,5-di-t-butyl-4-hydroxybenzoate, 2,4-di-t-butylphenyl-3',5'-di-t-butyl-4'-hydroxybenzoate, bis(2,2,6,6-tetramethyl-4-piperidyl)sebacate, dimethyl succinate-2-(4-hydroxy-2,2,6,6-tetramethyl-1-piperidyl)ethanol condensate, poly{[6-[(1,1,3,3-tetramethylbutyl)acetate] and light stabilizers such as N,N'-bis(3-aminopropyl)ethylenediamine-2,4-bis[N-butyl-N-(1,2,2,6,6-pentamethyl-4-piperidyl)amino]-6-chloro-1,3,5-triazine condensate.

[0060] Further examples include amine-based antioxidants represented by the following formula (2) or (3), which have good resistance to NOx gas discoloration, lactone-based antioxidants such as 5,7-di-t-butyl-3-(3,4-di-methyl-phenyl)-3H-benzofuran-2-one, and vitamin E-based antioxidants represented by the following formula (4).

[0061] [ka] (2)

[0062] [ka] (3)

[0063] [ka] (4)

[0064] Examples of neutralizing agents include metal fatty acid salts such as calcium stearate, zinc stearate, and magnesium stearate; hydrotalcite (trade name: DHT-4A, a magnesium aluminum composite hydroxide salt represented by the following formula (5) manufactured by Kyowa Chemical Industry Co., Ltd.); Mizukalac (trade name, a lithium aluminum composite hydroxide salt represented by the following formula (6) manufactured by Mizusawa Chemical Industry Co., Ltd.); and the like. Mg 1-x Al x (OH)2(CO3) x / 2 ·mH2O …(5) [In the formula, x satisfies 0 < x ≤ 0.5, and m is a number of 3 or less.] [Al2Li(OH)6] n X·mH2O …(6) [In the formula, X is an inorganic or organic anion, n is the valence of the anion (X), and m is 3 or less.]

[0065] Furthermore, various known additives, such as antistatic agents, lubricants, dispersants such as fatty acid metal salts, dyes, and pigments, can be blended within a range that does not impair the object of the present invention.

[0066] Within a range that does not impair the properties, functions, and other characteristics of the propylene-based polymer composition of the present invention, other polymers, polyethylene, ethylene-propylene copolymer, ethylene-propylene-diene copolymer, ethylene-1-butene copolymer, ethylene-vinyl acetate copolymer, ethylene-acrylate copolymer, acrylate polymer, and the like, such as homopolymers, copolymers of two components, and copolymers of three components, can be arbitrarily added in an amount of 1 to 30 parts by weight based on 100 parts by weight of the propylene-based polymer composition. Similarly, elastomers such as natural rubber, butyl rubber, diene rubber, EPR, and EPDM can also be blended. Furthermore, general-purpose inorganic fillers such as talc, calcium carbonate, silica, alumina, gypsum, and mica can also be used in combination.

[0067] (7) Flexural modulus of the propylene-based polymer composition The flexural modulus of the propylene-based polymer composition used in the present invention is preferably in the range of 1000 to 1500 MPa, and when the flexural modulus is 1000 MPa or more, the mold releasability from a mold during injection molding is good, and when it is 1500 MPa or less, the impact resistance is good, more preferably 1100 to 1450 MPa, and further preferably 1200 to 1400 MPa.

[0068] (8) Charpy impact strength of propylene polymer composition The Charpy impact strength of the propylene-based polymer composition used in the present invention is preferably 3.0 kJ / m 2 The Charpy impact strength is 3.0 kJ / m or more. 2 If the strength is more than this, damage to the molded product during transportation is suppressed. More preferably, it is 3.5 kJ / m 2 More preferably, it is 4.0 kJ / m 2 That's all.

[0069] (9) Haze of Propylene Polymer Composition The haze of the propylene-based polymer composition used in the present invention at a product thickness of 2 mmt is preferably in the range of 50% or less, and when the haze is 50% or less, the visibility of the contents is improved and the design is further improved, more preferably 45% or less, and further preferably 35% or less.

[0070] [2] Method for producing propylene polymer composition The propylene polymer composition of the present invention can be obtained by mixing the propylene (co)polymer (a), the propylene copolymer (b), the biomass polyethylene (c), and, if necessary, other additives in predetermined amounts in a Henschel mixer (trade name), a super mixer, a ribbon blender, or the like, and then melt-kneading the mixture in a temperature range of 190 to 260°C in a conventional single-screw extruder, twin-screw extruder, Banbury mixer, a plabender, a roll, or the like.

[0071] [3] Molded products obtained using the propylene polymer composition To produce a molded article using the propylene polymer composition of the present invention, the propylene polymer composition is molded into a molded article having a desired shape by injection molding or the like. The uses of the molded articles are not particularly limited, but they can be used in a wide range of applications, such as various industrial materials, automobile-related parts, various medical and cosmetic containers, daily necessities, films, and fibers. EXAMPLES

[0072] EXAMPLES The present invention will be described in detail below with reference to examples and comparative examples, but the present invention is not limited to these examples. In the following examples and comparative examples, the physical properties of the propylene (co)polymer (a), the propylene copolymer (b) and the propylene polymer composition were measured according to the following methods. <1. Measurement method>

[0073] (1) Melt flow rate (MFR): Measurements were performed in accordance with JIS K7210 (230°C, 2.16 kg load).

[0074] (2) Calculation of the ethylene content of the propylene (co)polymer (a) and the propylene copolymer (b) 13 The ethylene-propylene random copolymer, the composition of which was verified by C-NMR, was used as the standard substance. -1 The ethylene content in the random copolymer was measured by infrared spectroscopy using the characteristic absorption band of the following: The pellets were pressed into a film of about 500 μm thickness.

[0075] (3) Measurement of molecular weight and molecular weight distribution: The molecular weight distribution Mw / Mn of the propylene-based (co)polymer (a) and the propylene-based copolymer (b) was calculated by measuring the weight average molecular weight Mw and the number average molecular weight Mn by gel permeation chromatography (GPC) under the following measurement conditions: Apparatus: WATERS GPC (ALC / GPC 150C) Detector: FOXBORO MIRAN 1A IR detector (measurement wavelength: 3.42 μm) Column: Showa Denko AD806M / S (3 columns in series) Mobile phase solvent: ο-dichlorobenzene Measurement temperature: 140℃ Flow rate: 1.0ml / min Injection amount: 0.2ml

[0076] (4) Melting peak temperature (melting point) (Tm, unit: ° C.): Using a differential scanning calorimeter (DSC), a 5.0 mg sample was taken, the temperature was raised to 200°C once to erase the thermal history, and then the sample was held at 200°C for 5 minutes. The temperature was then lowered to 40°C at a rate of 10°C / min to crystallize the sample, and the temperature was then increased again at a rate of 10°C / min to melt the sample. The temperature at the top of the endothermic peak was recorded as the melting peak temperature (melting point) (Tm).

[0077] (5) Flexural modulus Measurements were performed in accordance with JIS K7171.

[0078] (6) Charpy impact strength The Charpy impact strength at 23°C was measured in accordance with JIS K7111. (7) Haze value Measurements were performed in accordance with JIS K7136 using a 2 mm thick sheet piece.

[0079] (8) Crack test in MD and TD directions Test pieces measuring 120 mm x 120 mm x 2 mm were injection molded (molding temperature: 200°C, mold temperature: 40°C) and a 3 cm long cut was made in each piece with pruning shears to a width of 1.5 cm as shown in Figure 2. The cut parts were then bent by hand and evaluated for cracks using the following criteria. ◎: Even if bent more than 90 degrees, no splits (fissures, cracks) will occur and the product will not separate into several parts. (No splits) ○: Even if it is bent more than 90 degrees, a split (crack) occurs, but it does not separate into several parts. (Does not split) ×: When bent more than 90 degrees, it separates into several parts (cracks).

[0080] <2. Resins and additives> 2-1. Production of propylene (co)polymer (a) (1) Manufacturing Example 1 (i) Preparation of solid catalyst A 100-liter reactor equipped with an agitator, a thermometer, a jacket, and a cooling coil was charged with Mg(OEt)2:30 mol, and then Ti(OBu)4 was charged so that Ti(OBu)4 / Mg=0.60 (mr (molar ratio)) was obtained with respect to the magnesium in the charged Mg(OEt)2. Furthermore, 19.2 kg of toluene (TOL) was charged and the temperature was raised while stirring. After reacting for 3 hours at 139°C, the temperature was lowered to 130°C, and a toluene solution of MeSi(OPh)3 was added so that MeSi(OPh)3 / Mg=0.67 (mr) was obtained with respect to the magnesium in the previously charged Mg(OEt)2. The amount of toluene used here was 7.8 kg. After the addition was completed, the reaction was carried out at 130°C for 2 hours, and then the temperature was lowered to room temperature, and Si(OEt)4 was added. The amount of Si(OEt)4 added was set to be Si(OEt)4 / Mg=0.056(mr) relative to the magnesium in the Mg(OEt)2 previously charged.

[0081] Next, toluene was added to the obtained reaction mixture so that the magnesium concentration was 0.58 (mol / L-TOL). Furthermore, diethyl phthalate (DEP) was added so that DEP / Mg=0.10 (mr) was obtained with respect to the magnesium in the Mg(OEt)2 previously charged. The obtained mixture was cooled to 10°C while continuing to stir, and TiCl4 was added dropwise over 2 hours to obtain a homogeneous solution. Note that TiCl4 was adjusted so that TiCl4 / Mg=4.0 (mr) was obtained with respect to the magnesium in the Mg(OEt)2 previously charged. After the addition of TiCl4 was completed, the temperature was raised to 15°C at 0.5°C / min while stirring, and the temperature was maintained at the same temperature for 1 hour. Next, the temperature was raised again to 50°C at 0.5°C / min, and the temperature was maintained at the same temperature for 1 hour. The temperature was further raised to 118°C at 1°C / min, and the treatment was performed at the same temperature for 1 hour. After the treatment was completed, the stirring was stopped, the supernatant liquid was removed, and the residue was washed with toluene to a residual liquid ratio of 1 / 73 (volume ratio of toluene / solid component) to obtain a slurry of the solid component.

[0082] Next, toluene and TiCl4 were added to the slurry obtained here at room temperature. The TiCl4 was adjusted so that TiCl4 / Mg(OEt)2=5.0(mr) relative to the magnesium in the Mg(OEt)2 previously charged. The toluene was adjusted so that the TiCl4 concentration was 2.0(mol / L-TOL). The slurry was heated while being stirred, and reacted at 118°C for 1 hour. After the reaction was completed, the stirring was stopped, the supernatant liquid was removed, and the mixture was washed with toluene so that the residual liquid ratio was 1 / 150 (volume ratio of toluene / solid component), and a slurry of solid components was obtained.

[0083] (ii) Preparation of solid catalyst component (A) Of the solid components obtained in (i), 400 g was transferred to another reactor equipped with an agitator, a thermometer, and a cooling jacket, and normal hexane was added to dilute the solid component to a concentration of 5.0 (g / l). Trimethylvinylsilane, TEA, and TBMDES were added to the obtained slurry at 15°C while stirring. TEA represents triethylaluminum, TBMDES represents t-butylmethyldiethoxysilane, and t-butyl represents a tertiary butyl group. The amounts of TEA, trimethylvinylsilane, and TBMDES added were 0.475 g, 0.137 g, and 0.167 g per 1 g of the solid component in the solid catalyst component (A), respectively. After the addition was completed, the mixture was kept at 15°C for 1 hour while continuing to stir, and then heated to 30°C and stirred at the same temperature for 2 hours. Next, the temperature was lowered again to 15°C, and while maintaining the same temperature, 4.8 kg of propylene gas was fed at a constant rate into the gas phase of the reactor over 8 hours to carry out prepolymerization. After the feeding was completed, stirring was stopped, the supernatant liquid was removed, and the mixture was washed with normal hexane to obtain a slurry of solid catalyst component (A). The residual liquid rate was 1 / 12 (volume ratio of normal hexane / solid catalyst component (A)). The obtained solid catalyst component (A) had 12.0 g of propylene polymer per 1 g of solid catalyst component (A).

[0084] (iii) Production of propylene-ethylene copolymers Internal volume 0.4m 3A continuous production of propylene-ethylene copolymer was carried out by a process incorporating a degassing system consisting of a double-tube heat exchanger and a fluidized flash tank in the downstream of a liquid-phase polymerization tank equipped with an agitator. Liquefied propylene, ethylene, hydrogen, TEA, and TBEDMS were continuously fed to the liquid-phase polymerization tank. TBEDMS stands for t-butylethyldimethoxysilane, and t-butyl stands for a tertiary butyl group. The feed rates of liquefied propylene, TEA, and TBEDMS were 163 kg / hr, 8.86 g / hr, and 1.37 g / hr, respectively, and hydrogen and ethylene were fed so that their gas phase concentrations were 6.15 mol% and 0.74 mol%, respectively. Furthermore, the solid catalyst component (A) obtained in (ii) above was fed to 0.13 g / hr as the solid component contained in (A). The liquid-phase polymerization tank was cooled so that the polymerization temperature was 70°C. The slurry polymerized in the liquid phase polymerization tank was heated by a double-pipe heat exchanger and discharged into a fluidized flash tank. The discharge rate of the slurry was adjusted to about 24 kg / hr as polypropylene particles contained in the slurry. The average residence time of the polypropylene particles in the liquid phase polymerization tank was 1.4 hours. Analysis of the discharged polypropylene showed that the MFR was 25.0 g / 10 min, the ethylene content was 0.7 wt%, the molecular weight distribution (Mw / Mn) was 5.7, and the Tm was 156°C.

[0085] (2) Manufacturing Example 2 (i) Preparation of solid catalyst 20 L of dehydrated and deoxygenated n-heptane was introduced into a 50 L tank equipped with a stirrer and thoroughly purged with nitrogen, followed by 10 moles of magnesium chloride (MgCl2) and 20 moles of tetrabutoxytitanium [Ti(On-C4H9)4], and the reaction was carried out at 95°C for 2 hours. After the reaction was completed, the temperature was lowered to 40°C, and methylhydropolysiloxane [kinetic viscosity: 20 centistokes (cSt) = 2 x 10 -5 m 2 12 L of 1,2-dichloroethane (1000 mL / s) was introduced and reacted for 3 hours. The resulting solid component was washed with n-heptane. Next, 5 L of n-heptane purified in the same manner as above was introduced into the tank equipped with the stirrer, and 3 moles of the solid component synthesized above were introduced in terms of Mg atom. Next, 5 moles of tetrachlorosilane (SiCl4) were mixed with 2.5 L of n-heptane, introduced into the flask at 30°C for 30 minutes, and reacted at 70°C for 3 hours. After the reaction was completed, the mixture was washed with n-heptane. Next, 2.5 L of n-heptane was introduced into the tank equipped with the stirrer, and 0.3 moles of phthalic acid chloride was mixed and introduced at 70°C for 30 minutes, and reacted at 90°C for 1 hour. After the reaction was completed, the reaction mixture was washed with n-heptane. Then, 2 L of titanium tetrachloride (TiCl4) was introduced and reacted at 110°C for 3 hours. After the reaction was completed, the reaction mixture was washed with n-heptane to obtain a solid component (b1) for preparing a solid catalyst component (b). The titanium content of this solid component (b1) was 2.0% by weight. Then, 8 L of n-heptane, 400 g of the solid component (b1) synthesized above, and 0.6 L of SiCl4 as component (b2) were introduced into the nitrogen-purged agitator-equipped tank, and the reaction was carried out for 2 hours at 90° C. After the reaction was completed, 0.54 mol of vinyltrimethylsilane [(CH2=CH)Si(CH3)3] as component (b3), 0.27 mol of t-butylmethyldimethoxysilane [(t-C4H9)(CH3)Si(OCH3)2] as component (b4), and 1.5 mol of triethylaluminum [Al(C2H5)3] as component (a5) were sequentially introduced, and the reaction was carried out for 2 hours at 30° C. After the contact, the mixture was thoroughly washed with n-heptane to obtain 390 g of a solid catalyst component (b) mainly composed of magnesium chloride. The titanium content of this solid catalyst component (b) was 1.8% by weight.

[0086] (ii) Prepolymerization The solid catalyst component (b) obtained above was used to carry out preliminary polymerization according to the following procedure. Purified n-heptane was introduced into the above slurry to adjust the concentration of the solid catalyst component (b) to 20 g / L. After cooling the slurry to 10°C, 10 g of n-heptane diluted solution of Al(C2H5)3 was added as Al(C2H5)3, and 210 g of propylene was fed over 4 hours. After the propylene feed was completed, the reaction was continued for another 30 minutes. Next, the gas phase was thoroughly replaced with nitrogen, and the reaction product was thoroughly washed with purified n-heptane. The resulting slurry was extracted from the autoclave and vacuum dried to obtain a prepolymerized solid catalyst component (B). This solid catalyst component (B) contained 2.0 g of polypropylene per 1 g of solid catalyst component (B). Analysis revealed that the portion of this solid catalyst component (B) excluding polypropylene contained 1.0 wt% Ti and 8.2 wt% (i-C3H7)2Si(OCH3)2.

[0087] (iii) Production of propylene homopolymer Propylene polymerization was carried out using a fluidized bed reactor with an internal volume of 230 L as a continuous reactor. Propylene and hydrogen were continuously fed into the reactor so that the polymerization temperature was 85° C., the propylene partial pressure was 1.8 MPa (absolute pressure), and hydrogen as a molecular weight regulator was 0.010 in molar ratio of hydrogen / propylene. Furthermore, 5.25 g / hour of triethylaluminum and 0.50 g of the above-described prepolymerized solid catalyst component (B) were fed so that the propylene polymerization rate was 20 kg / hour, to produce a propylene homopolymer. The powder polymerized in the reactor was continuously discharged into a vessel so that the amount of powder held in the reactor was 60 kg. The reaction was stopped by supplying nitrogen gas containing moisture, and a propylene homopolymer was obtained. The MFR of this propylene homopolymer was 9 g / 10 min.

[0088] 2-2. Propylene-based (co)polymer (a) (PP-1) Propylene-based resin obtained by polymerization in Production Example 1 (PP-2) Propylene-based resin obtained by polymerization in Production Example 2 2-3. Propylene-based copolymers other than (b) (PP-3) Japan Polypropylene Corporation, trade name "WINTEC WMG03", MFR = 30g / 10min, ethylene content = 0.9wt%, Tm = 142°C 2-4. Propylene copolymer (b) (PP-4) Japan Polypropylene Corporation, trade name "WINTEC WFW4M", MFR = 7.0g / 10min, ethylene content = 1.9wt%, Tm = 135°C (PP-5) Product name "NOVATEC PP MG03BD" manufactured by Japan Polypropylene Corporation, MFR = 30g / 10min, ethylene content = 2.4% by weight, Tm = 152°C

[0089] 2-5. Biomass polyethylene (c) Low Density Polyethylene (LDPE) (PE-1)Braskem product name "Green PE SPB608" Density: 0.915g / cm 3 , melt flow rate according to ASTM D1238 (190℃, 2.16kg load) is 30g / 10min, bio content: 95%. (All properties are listed in the manufacturer's catalogue.) Linear Low Density Polyethylene (LLDPE) (PE-2)Braskem product name "Green PE SLL118" Density: 0.916g / cm 3 , melt flow rate according to ASTM D1238 (190℃, 2.16kg load) is 1g / 10min, bio content: 87%. (All properties are listed in the manufacturer's catalogue.) High Density Polyethylene (HDPE) (PE-3)Braskem product name "Green PE SGM9450F" Density: 0.952g / cm 3 The melt flow rate conforming to ASTM D1238 (190℃, 5kg load) is 0.33g / 10min, and the bio content is 96%. (All properties are listed in the manufacturer's catalogue.)

[0090] 2-6. Other additives (A-1) Hindered phenol antioxidant "IR1010" Tetrakis[methylene-3-(3',5'-di-t-butyl-4'-hydroxylphenyl)propionate]methane. Manufactured by BASF Japan Ltd., product name "IRGANOX1010". (A-2) Phosphorus-based antioxidant "IF168" Tris(2,4-di-t-butylphenyl)phosphite. Manufactured by BASF Japan Ltd., product name "IRGAFOS168". (B-1) Neutralizer "CAST" calcium stearate. Manufactured by NOF Corporation. (N-1) Nucleating agent "NX8000J" 1,2,3-trideoxy-4,6:5,7-bis-[(4-propylphenyl)methylene]-nonitol. Manufactured by Milliken & Company, trade name "Milad NX8000J".

[0091] <3. Examples 1 to 10 and Comparative Examples 1 to 9> Each polymer and additive were prepared in the mixing ratio (parts by weight) shown in Table 1, dry-blended in a super mixer, and then melt-kneaded in a nitrogen atmosphere at a die outlet temperature of 220°C using a Toshiba Machine TEM-35B twin-screw extruder, and pelletized. The physical properties of the resulting pellets were measured. The evaluation results are shown in Table 1.

[0092] [Table 1]

[0093] As is clear from Table 1, Examples 1 to 10 contain the specified amounts of the propylene-based (co)polymer (a), propylene-based copolymer (b) and biomass polyethylene (c) according to the present invention, and are materials that can reduce environmental loads, and are excellent in rigidity and do not crack. Example 1 contains a specified amount of LDPE as the biomass polyethylene (c), and is also excellent in transparency. Example 2 is the composition of Example 1 in which the content of the biomass polyethylene (c) LDPE is reduced, and is more excellent in rigidity and transparency than Example 1. Examples 3 and 4 use LLDPE and HDPE as the biomass polyethylene (c), respectively, and Examples 5 to 7 use propylene homopolymer as the propylene-based (co)polymer (a). Examples 8 to 9 increase or decrease the content of the propylene-based copolymer (b), and Example 10 uses a different propylene-based copolymer (b), but it can be confirmed that the effects of the present invention are obtained. On the other hand, Comparative Examples 1 and 2 have a lower α-olefin content than the propylene-based copolymer (b) or do not contain the propylene-based copolymer (b), and although the rigidity is slightly better than that of Example 1, it is found that the cracking test in the TD direction cracks. Comparative Examples 3 and 4 are compositions containing PP-1 or PP-4 alone, but the biomass degree is 0%. Comparative Example 5 is a composition containing PE-1 alone, and the rigidity is insufficient. Comparative Example 6 has a low content of the propylene-based copolymer (b), so it cracks in the TD direction, and Comparative Example 9 has a high content of the propylene-based copolymer (b), so it is insufficient in rigidity. Comparative Example 7 has a low content of the biomass polyethylene (c), so the biomass degree is too low, and Comparative Example 8 does not use the propylene-based copolymer (b), so it is found that the cracking test in the TD direction cracks. [Industrial Applicability]

[0094] The propylene-based polymer composition of the present invention gives molded articles that are excellent in rigidity and do not crack even when it contains biomass polyethylene, and since the biomass content is 8.4 to 49%, it is useful for reducing the environmental load.

Claims

1. A propylene-based polymer composition for injection molding contains 26 to 87 parts by weight of a propylene-based (co)polymer (a) satisfying the following conditions (Hi) to (H-ii), 3 to 25 parts by weight of a propylene-based copolymer (b) satisfying the following conditions (A-i) to (A-iii), and 10 to 49 parts by weight of a biomass polyethylene (c), totaling 100 parts by weight, and having a biomass degree of 8.4 to 49%. (Hi) A propylene homopolymer or a propylene copolymer comprising propylene and an α-olefin in an amount of less than 1% by weight. (H-ii) The melt flow rate (hereinafter sometimes abbreviated as MFR) according to JIS K7210 (230° C., 2.16 kg load) is in the range of 0.5 to 100 g / 10 min. (Ai) Propylene-α-olefin random copolymer. (A-ii) The α-olefin content is in the range of 1% by weight or more and less than 3% by weight. (A-iii) The MFR is in the range of 0.5 to 80 g / 10 min.

2. The propylene-based polymer composition for injection molding according to claim 1, wherein the propylene-based copolymer (b) satisfies the following conditions (A-iv) to (A-v): (A-iv) Metallocene-based propylene-ethylene random copolymer. (Av) The melting peak temperature (Tm) is in the range of 126°C or higher and lower than 142°C.

3. 3. A propylene-based polymer composition for injection molding, comprising 0.01 to 0.6 parts by weight of a nucleating agent based on 100 parts by weight of the propylene-based polymer composition for injection molding according to claim 1 or 2.

4. A molded article obtained by using the propylene polymer composition for injection molding according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Propylene-based resin composition for injection molding and molded article

    JP2015140422A

  • Polyolefin resin film

    JP2016027171A

  • Polypropylene resin composition, spin-dyeing material using the same as raw material, and molded body using the same as raw material

    JP2017075209A

  • Laminate for packaging

    JP2019034519A

  • Packaging bag

    JP2019059511A